2007
DOI: 10.1016/j.cellbi.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Muscle actin isoforms are differentially expressed in human satellite cells isolated from donors of different ages

Abstract: Myogenesis is mainly sustained by a subpopulation of myogenic cells known as satellite cells (SC). In this paper we studied alpha-smooth muscle (alphaSMA) and alpha-sarcomeric muscle (alphaSRA) actin isoform expression in cultures of human satellite cells (HSC) isolated from skeletal muscle biopsies from a 5-day-old newborn, a 34-year-old young adult and a 71-year-old donor. Myogenicity of cultures was assessed using immunocytochemical detection of desmin and myosin heavy chain. Time-course expression of alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…5A, red arrows). The “rounded” and “flattened” myoblasts were examined in more detail by confocal imaging after staining with antibodies to smooth muscle actin (SMA), which is expressed transiently in undifferentiated myoblasts [41, 60]. The flattened morphology was associated with cell spreading, filamentous actin redistribution, and increased numbers of cell surface protrusions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5A, red arrows). The “rounded” and “flattened” myoblasts were examined in more detail by confocal imaging after staining with antibodies to smooth muscle actin (SMA), which is expressed transiently in undifferentiated myoblasts [41, 60]. The flattened morphology was associated with cell spreading, filamentous actin redistribution, and increased numbers of cell surface protrusions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, this concept has been confirmed and discussed by four further papers (three original works and one review), again collectively suggesting that muscle‐derived cells retain a ‘memory’ of negative encounters once isolated from different environmental niches, where (i) muscle‐derived cells from obese patients do not respond to lipid oversupply with the same gene expression signatures vs. control (Maples & Brault, ); (ii) muscle‐derived cells from intrauterine growth‐restricted sheep foetuses exhibit deficiencies in proliferation vs. controls (Yates et al ., ); (iiii) skeletal muscle stem cells isolated from prenatal 50% global nutrient‐restricted mice offspring or early postnatal high‐fat diet (60% of total calories from fat) offspring have a reduced number of muscle precursor cells and a 32% decrease in the capacity of these cells to regenerate after injury (Woo et al ., ). Interestingly, in the same study it was reported that a high‐fat diet also evoked reductions in the number of muscle stem cells retrieved from skeletal muscle tissue and was associated with larger reductions (44%) in regeneration (chow 16% vs. high‐fat diet 9%), suggesting that the environment in which the muscle cells were derived could be remembered and subsequently affect the muscle repair and regeneration in later life (Woo et al ., ); (iv) finally, the vast majority of aged muscle stem cells isolated from aged animals and humans or those replicatively aged in culture have an impaired or delayed differentiation/regenerative capacity (Allen et al ., ; Charge et al ., ; Lorenzon et al ., ; Lees et al ., ; Carlson & Conboy, ; Lancioni et al ., ; Bigot et al ., ; Hidestrand et al ., ; Pietrangelo et al ., ; Beccafico et al ., ; Sharples et al ., , , ; Kandalla et al ., ; Merritt et al ., ; Zwetsloot et al ., ) or display delayed differentiation (Corbu et al ., ). Very few studies showed no impact of age on differentiation of the isolated muscle stem cells (Shefer et al ., ; Alsharidah et al ., ); where even these studies reported aged muscle to have fewer stem cells to begin with (Shefer et al ., ).…”
Section: Muscle Cellular Memory: Evidence From Animal Tissue Models Amentioning
confidence: 99%
“…This included altered methylation of MyoD 24 , Myogenin 25 and Six1 26 . While muscle stem cells derived from aged individuals display similar proliferative capacity and time to senescence as young adult cells 27,28 , they do have impaired differentiation and fusion into myotubes 29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45 . However, a small number of studies did not find an effect of age on the differentiation capacity of isolated cells 27,46,47 .…”
mentioning
confidence: 99%